Manajemen Partisipatif: Sebuah Pendekatan Meningkatkan Peran Masyarakat Dalam Pembangunan Desa - M. Harry Mulya Zein; Sisca Septiani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2021)
Village development will not be separated from community participation because it is the primary beneficiary of development and becomes a development actor. This study examines exploring planning to participatory evaluation involving rural communities in evaluating village development programs. This makes it possible to provide feedback, monitor progress, and identify changes needed to implement development programs. The study used a qualitative approach, using primary data from interviews and relevant secondary data. The results of community research are included in village development planning through Musrembang. In the implementation stage of community development, they are also involved even though not all communities participate in the village development process. Participatory management in development in Liunggunung Village is in the infrastructure development approach and other fields such as health. The community is involved and contributes to infrastructure development and other fields. Community participation can lead to empowering rural communities, increasing their decision-making capacity, and strengthening social networks in communities. Communities involved in the decision-making and implementation of village development projects tend to have a higher sense of ownership of the project. The active participation of the community in village development has a positive impact on the sustainability of the program and the improvement of the community's quality of life. Community participation in village development is essential for sustainable development, community empowerment, and improved quality of life locally.